2020
DOI: 10.26480/sfna.02.2020.69.75
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF DIFFERENT POSTHARVEST TREATMENTS ON PROLONGING SHELF LIFE AND MAINTAINING QUALITY OF SWEET ORANGE (Citrus sinensis Osbeck.)

Abstract: An experiment was conducted to evaluate the effect of different postharvest treatments on maintaining quality and shelf life of sweet orange from Feb-Apr 2019 under completely randomized (CRD) with four replications and five treatments (T1= Aloe vera gel @100%, T2= Paraffin wax @100%, T3= Corn Starch @4%, T4=Tragacanth Gum @4%, T1=Control i.e. untreated fruits) at ambient room condition (15.15±0.33ºC, 58.16±1.69% RH). The parameters recorded were Physiological loss in weight (PLW), total soluble solid(TSS), ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…The might be due to loss of moisture from the surface of sweet orange fruit packed in different packaging materials and stored under cold storage conditions showed a low reduction in juice content during storage as compared untreated control under room temperature where polyethylene acted as a barrier which had checked the losses of the moisture from the fruit surface (Dar and Nayik, 2022). The results of present findings are in parallel with results reported by Ahmad et al (2013) in sweet orange, Dhumal et al (2008) in aonla, Thapa et al (2020) in sweet orange and Isnaini and Purbiati (2021) in tangerine.…”
Section: Juice Content (%)supporting
confidence: 93%
“…The might be due to loss of moisture from the surface of sweet orange fruit packed in different packaging materials and stored under cold storage conditions showed a low reduction in juice content during storage as compared untreated control under room temperature where polyethylene acted as a barrier which had checked the losses of the moisture from the fruit surface (Dar and Nayik, 2022). The results of present findings are in parallel with results reported by Ahmad et al (2013) in sweet orange, Dhumal et al (2008) in aonla, Thapa et al (2020) in sweet orange and Isnaini and Purbiati (2021) in tangerine.…”
Section: Juice Content (%)supporting
confidence: 93%
“…Data presented in Table (5) revealed that titratable acidity percentage decreased with the advancement of the storage period. This result was conformable with the result of Thapa et al [27] who concluded that the increase of the storage period decreased significantly the titratable acidity content of sweet orange fruits.…”
Section: Titratable Acidity Percentagesupporting
confidence: 92%
“…Data presented in Table (1) clearly indicated that weight loss percentage increased gradually and significantly with extending cold storage period with significant differences among them during the two successive seasons. This result was in the same line of Thapaa et al [27] who confirmed that the advancement of storage period was accompanied by an increase in weight loss percentage of sweet orange fruits. The least value of the weight loss percentage (9.22 and 10.54%) was obtained by irradiated cassava starch followed by irradiated sweet potato starch (9.40 and10.86%) in the first and second seasons.…”
Section: Fruit Weight Loss Percentagesupporting
confidence: 88%
“…Joshi et al (2020) obtained more juice recovery in mandarin treated with wax as compared to others. Thapa et al (2020) in sweet orange also obtained more juice content by wax treatment as compared to others.…”
Section: Effect Of Different Edible Coatings On Juice Contentmentioning
confidence: 70%
“…It might be because wax retarded the transpiration and respiration by closing lenticels and stomata of the cell wall of the fruit skin (Rokaya et al, 2016). Ahmad et al (2013), Sahu (2016), Joshi et al(2020 and Thapa et al (2020) obtained minimum physiological weight losses in Kinnow fruit, custard apple, mandarin and sweet orange fruit, respectively, by wax treatment. As expected, the physiological loss in weight increased upon daily storage in all treatments (Table 2) due to the continuous loss of moisture caused by the transpiration and respiration process (Nath et al, 2011).…”
Section: Results and Discussion Effect Of Different Edible Coatings On Physiological Loss In Weight (Plw %)mentioning
confidence: 99%